The Influence Of Promotions And Consumer Perceptions On The Decision To Repurchase Xpander Cars In Tasikmalaya (Survey on Consumers of Mitsubishi Xpander in Tasikmalaya) - Rina Erliyana; Depy Muhamad Pauzy; Suci Putri Lestari (Jurnal Fokus Manajemen, 2022)
This study aims to determine the effect of promotions and consumer perceptions on the decision to repurchase Xpander cars in Tasikmalaya. The type of research used is quantitative research with causality method and survey approach. Sampling using non-probability sampling that is purposive sampling as many as 100 respondents using multiple linear regression analysis techniques. The results of this study indicate that promotion and consumer perception simultaneously have a significant effect on repurchase decision for Xpander cars in Tasikmalaya. Promotions and consumer perceptions partially have a significant effect on repurchase decision for Xpander cars in Tasikmalaya.